Tick-Tattoo: DNA Vaccination Against B. burgdorferi or Ixodes scapularis Tick Proteins - Klouwens, Michelle J.; Trentelman, Jos J. A.; Wagemakers, Alex; Ersoz, Jasmin I.; Bins, Adriaan D.; Hovius, Joppe W. (Frontiers in Immunology, 2021)
Introduction Borrelia burgdorferi sensu lato (sl) is the causative agent of Lyme borreliosis. Currently there is no human vaccine against Lyme borreliosis, and most research focuses on recombinant protein vaccines. DNA tattoo vaccination with B. afzelii strain PKo OspC in mice has proven to be fully protective against B. afzelii syringe challenge and induces a favorable humoral immunity compared to recombinant protein vaccination. Alternatively, several recombinant protein vaccines based on tick proteins have shown promising effect in tick-bite infection models. In this study, we evaluated the efficacy of DNA vaccines against Borrelia OspC or tick antigens in a tick-bite infection model. Method We vaccinated C3H/HeN mice with OspC using a codon-optimized DNA vaccine or with recombinant protein. We challenged these mice with B. burgdorferi sensu stricto (ss)-infected Ixodes scapularis nymphs. Subsequently, we vaccinated C3H/HeN mice with DNA vaccines coding for tick proteins for which recombinant protein vaccines have previously resulted in interference with tick feeding and/or Borrelia transmission: Salp15, tHRF, TSLPI, and Tix-5. These mice were also challenged with B. burgdorferi ss infected Ixodes scapularis nymphs. Results DNA tattoo and recombinant OspC vaccination both induced total IgG responses. Borrelia cultures and DNA loads of skin and bladder remained negative in the mice vaccinated with OspC DNA vaccination, except for one culture. DNA vaccines against tick antigens Salp15 and Tix-5 induced IgG responses, while those against tHRF and TSLPI barely induced any IgG response. In addition, Borrelia cultures, and DNA loads from mice tattooed with DNA vaccines against tick proteins TSLPI, Salp15, tHRF, and Tix-5 were all positive. Conclusion A DNA tattoo vaccine against OspC induced high specific IgG titers and provided near total protection against B. burgdorferi ss infection by tick challenge. In contrast, DNA tattoo vaccines against tick proteins TSLPI, Salp15, tHRF, and Tix-5 induced low to moderate IgG titers and did not provide protection. Therefore, DNA tattoo vaccination does not seem a suitable vaccine strategy to identify, or screen for, tick antigens for anti-tick vaccines. However, DNA tattoo vaccination is a straightforward and effective vaccination platform to assess novel B. burgdorferi sl antigen candidates in a relevant tick challenge model.